Framing the Absence and Presence of Rebecca: Female Subjectivity and Voyeurism On and Off-Screen in Alfred Hitchcock’s Rebecca - Osoliová, Viktória (AMERICANA E-journal of American Studies in Hungary, 2021)
In this paper, I endeavour to explore how Alfred Hitchcock adapted in his first American feature film Daphne du Maurier’s famous novel, Rebecca from page to silver screen. After providing a film historical overview of the genre of women’s film of the 1930s and ‘40s and of cinematic appropriations of the gothic romance genre, I study the role of the look and the gaze, female subjectivity, and the trope of the gothic house in Hitchcock’s romantic psychological thriller film. I argue that Hitchcock’s special camera techniques reach uncanny effects by visualising the absent presence of the ghastly titular character.